Twenty years of editorial management in annals: Renaissance of Anales de la Facultad de Medicina - May 1995 - Piscoya Arbañil, José Leonardo (2015)
An account on Anales de la Facultad de Medicina re-edition in May 1995, difficulties and opportunities found, conformation of the Editorial Staff, and achievements attained during those five years is done.